تأثير وسيلة لعبة دومينو في فهم تصريف الأفعال لطلاب الفصل الحادي عشر بالمدرسة التربية الإسلامية باسر - Irhamni, Irhamni; Dewi, Yelfi; Yusra, Oktarina (The Future of Education Journal, 2026)
This thesis was prepared by Irhamni, registration number 2217011, Department of Arabic Language Education, Faculty of Education and Teacher Training, Bukit Tinggi State Islamic University. It is titled: " The Effect of the Domino Game on Understanding Verb Conjugation among Eleventh Grade Students at the Pasar Islamic Education School."The problems that exist in the courtyard are the placement of verbs that agree with their pronouns, even for students. The eleventh grade students at the Islamic Education School in Asir are experiencing difficulty . In their relationship when they meet Miscellaneous examples .The researcher used an experimental method. The data collection method was a pre-test and post-test in two semesters, and the data analysis was a t -test . Before the researcher used this method, the results of verb conjugation instruction showed that the average pre-test score in the experimental class was 70.15, and the pre-test score in the control class was 66.36. After using this method, the average post-test score in the experimental class was 83.78, and the post-test score in the control class was 73.48. The increase in the average score in the experimental class was 11.97 , and the increase in the control class was 7.12 . The researcher found the hypothesis that Looking in two directions (t-tailed) 0.005 , which is smaller than The 0.05 value indicates that the null hypothesis ( Ho ) is rejected, while the alternative hypothesis ( Ha ) is accepted. Based on the descriptive value, it appears that the experimental group's use of the domino game to understand verb conjugation in the eleventh grade at the Islamic Education School in Vaser is acceptable. The researcher concluded that using the domino game as a tool positively impacts the eleventh-grade students' understanding of verb conjugation at the Islamic Education School in Vaser.